PENGUATAN EDUPRENEURSHIP PESERTA DIDIK DI SMP NEGERI 49 SURABAYA DALAM MENGHADAPI TANTANGAN ERA SOCIETY 5.0 - Fitri Ilmilia Fuada; Ayunda Mahdalena Putri; Komang Raditya Adhistyananda; Raden Roro Nanik Setyowati; Siti Maizul Habibah; Anam Miftakhul Huda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Society 5.0 era requires educational institutions to produce students who are adaptive, creative, innovative, and capable of solving complex problems in response to technological advancement and societal needs. One approach that can support this goal is edupreneurship, which integrates entrepreneurial values into educational processes through contextual and meaningful learning experiences. This study aims to analyze the actualization of edupreneurship, school strategies in strengthening its implementation, and the challenges encountered at SMP Negeri 49 Surabaya. This research employed a descriptive qualitative approach using a case study method. Data were collected through observation, interviews, and documentation, then analyzed thematically. The findings reveal that the Kokurikuler Jawara 49 (Jajanan Wirausaha 49) program and waste-processing activities into creative products successfully foster students’ independence, self-confidence, responsibility, environmental awareness, and creative and innovative thinking skills. Teachers play significant roles as facilitators, motivators, and mentors in supporting experiential learning activities. Furthermore, the utilization of local resources in entrepreneurial projects provides authentic learning experiences that enhance students’ twenty-first-century competencies. Despite these achievements, several challenges remain, including low self-confidence among some students, disparities in digital literacy, and limitations related to facilities, time allocation, and continuous guidance. The study concludes that project-based and experiential edupreneurship is an effective strategy for preparing students to face the challenges of the Society 5.0 era. The implementation of such programs contributes not only to entrepreneurial competence but also to character development and social responsibility. These findings offer practical implications for schools seeking to strengthen entrepreneurship education and create sustainable learning environments that support the development of future-ready generations.